Quorum Sensing Inhibitors to Quench P. aeruginosa Pathogenicity - Marine Duplantier; Elodie Lohou; Pascal Sonnet (MDPI AG, 2021)
The emergence and the dissemination of multidrug-resistant bacteria constitute a major public health issue. Among incriminated Gram-negative bacteria, Pseudomonas aeruginosa has been designated by the WHO as a critical priority threat. During the infection process, this pathogen secretes various virulence factors in order to adhere and colonize host tissues. Furthermore, P. aeruginosa has the capacity to establish biofilms that reinforce its virulence and intrinsic drug resistance. The regulation of biofilm and virulence factor production of this micro-organism is controlled by a specific bacterial communication system named Quorum Sensing (QS). The development of anti-virulence agents targeting QS that could attenuate P. aeruginosa pathogenicity without affecting its growth seems to be a promising new therapeutic strategy. This could prevent the selective pressure put on bacteria by the conventional antibiotics that cause their death and promote resistant strain survival. This review describes the QS-controlled pathogenicity of P. aeruginosa and its different specific QS molecular pathways, as well as the recent advances in the development of innovative QS-quenching anti-virulence agents to fight anti-bioresistance.